Bioformulated to maintain the viability of rhizobacteria and their application in Theobroma cacao L. CCN-51 - Canchignia Martínez , Hayron Fabricio (2024)
Introduction. The use of bioformulated plant growth-promoting rhizobacteria is an alternative to reduce the dependence on pesticides in agriculture, due to their pathogen biocontrol and nutrient solubilizing action. Objective. To evaluate the effect of bioformulates on the cell viability of rhizobacteria and their effect on Theobroma cacao L. Materials and methods. The research was conducted from January to December 2020 in the Microbiology and Molecular Biology laboratories of the Universidad Técnica Estatal de Quevedo and at the Ignolia farm, located in La Maná, Ecuador. The following were evaluated: the potential characteristics of bacteria to be considered as rhizobacteria; the identification of the chiA gene through polymerase chain reaction; the effect of bioformulations on the cell viability of rhizobacteria; and their field application to assess the productivity and phytosanitary status of Theobroma cacao. Results. Rhizobacteria had the capacity to solubilize of nutrients, producers of hydrolytic and biofilm-generating enzymes. Eighty percent of the strains presented the chiA gene, with antifungal activity against pathogenic fungi. The BIOQPGPRs bioformulated with A. calcoaceticus, E. asburiae, S. marcescens, P. protegens and P. veronii showed greater cell persistence (1.83E+5, 1.80E+5, 1.63E+5 and 1.63E+5) during the 26 days. Its edaphic application and injection in the rainy season increased leaf emissions with 100 and 108, and reduce the incidence of Phytophthora spp. and its edaphic application of the bacterial consortium improve dry grain yield (1270.6 kg/ha). Conclusions. BIOQPGPRs preserved rhizobacteria with cell viability for 26 days. Its field application increased the number of foliar emissions, reduced the incidence of Phytophthora spp. on pods, and improved crop yield.